The Role of Extracellular Heat Shock Proteins in Cardiovascular Diseases - Soumya Patnaik; Sriram Nathan; Biswajit Kar; Igor D. Gregoric; Yi-Ping Li (Biomedicines, 2023)
In the early 1960s, heat shock proteins (HSPs) were first identified as vital intracellular proteinaceous components that help in stress physiology and reprogram the cellular responses to enable the organism’s survival. By the early 1990s, HSPs were detected in extracellular spaces and found to activate gamma-delta T-lymphocytes. Subsequent investigations identified their association with varied disease conditions, including autoimmune disorders, diabetes, cancer, hepatic, pancreatic, and renal disorders, and cachexia. In cardiology, extracellular HSPs play a definite, but still unclear, role in atherosclerosis, acute coronary syndromes, and heart failure. The possibility of HSP-targeted novel molecular therapeutics has generated much interest and hope in recent years. In this review, we discuss the role of Extracellular Heat Shock Proteins (Ec-HSPs) in various disease states, with a particular focus on cardiovascular diseases.